Licochalcone A inhibits MAS‐related GPR family member X2‐induced pseudo‐allergic reaction by suppressing nuclear migration of nuclear factor‐κB. (5th September 2021) - Xue, Zhuoyin; Zhang, Yongjing; Zeng, Yingnan; Hu, Shiling; Bai, Haoyun; Wang, Jue; Jing, Huiling; Wang, Nan
Abstract : Licochalcone A (Lico A) is a natural flavonoid belonging to the class of substituted chalcone that has various biological effects. Mast cells (MCs) are innate immune cells that mediate hypersensitivity and pseudo‐allergic reactions. MAS‐related GPR family member X2 (MRGPRX2) on MCs has been recognized as the main receptor for pseudo‐allergic reactions. In this study, we investigated the anti‐pseudo‐allergy effect of Lico A and its underlying mechanism. Substance P (SP), as an MC activator, was used to establish an in vitro and in vivo model of pseudo‐allergy. The in vivo effect of Lico A was investigated using passive cutaneous anaphylaxis (PCA) and active systemic allergy, along with degranulation, Ca 2+ influx in vitro. SP‐induced laboratory of allergic disease 2 (LAD2) cell mRNA expression was explored using RNA‐seq, and Lico A inhibited LAD2 cell activation by reverse transcription polymerase chain reaction (RT‐PCR), western blotting, and immunofluorescence staining. Lico A showed an inhibitory effect on SP‐induced MC activation and pseudo‐allergy both in vitro and in vivo. The nuclear factor (NF)‐κB pathway is involved in MRGPRX2 induced MC activation, which is inhibited by Lico A. In conclusion, Lico A inhibited the pseudo‐allergic reaction mediated by MRGPRX2 by blocking NF‐κB nuclear migration.